Expression of IL-33 in subjects with periodontitis: a systematic review and meta-analysis - Alarcón-Sánchez, Mario Alberto; Romero-Castro, Norma Samanta; Reyes-Fernández, Salvador; Sánchez-Tecolapa, Edgar Uriel; Heboyan, Artak (European journal of medical research, 2024)
Activation of the IL-33/ST2 axis leads to the production of proinflammatory cytokines and thus to the triggering of osteoclastogenesis, which is why it plays an important role in the immunopathogenesis of periodontitis. The aim of this study was to compare IL-33 levels in serum, plasma, saliva and gingival crevicular fluid (GCF) of subjects with chronic periodontitis (CP) in comparison with the control group (CG). This systematic review and meta-analysis followed the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) and was registered in the Open Science Framework (OSF): https://doi.org/10.17605/OSF.IO/YHUWA . Six electronic databases were used for study identification; PubMed, Google Scholar, ScienceDirect, Web of Science, Scopus and Dentistry & Oral Sciences Source from March 10, 2012 to April 30, 2024. The Joanna Briggs Institute (JBI) tool was used to assess the quality of the included cross-sectional articles and clinical trials. Of the 949 articles identified, 14 were included according to the inclusion and exclusion criteria. The total number of individuals studied in the included investigations was 814 of whom 445 had CP and 369 were healthy. The reported age range was from 20 to 50 years, with a mean age ± standard deviation of 40.29 ± 7.83 years. Four hundred and twenty-six (52%) patients were men and 388 (48%) were women. Meta-analysis revealed that there is an increase in IL-33 levels in plasma, saliva and GCF of subjects with CP compared to CG (p = * < 0.05). This study found a significant increase in IL-33 levels in different biological samples (plasma, saliva and GCF) of individuals with CP compared to CG, thus IL-33 has potential to be a biomarker in the diagnosis of periodontitis.